(untitled) (International Current Pharmaceutical Journal, 2017)
Four compounds were isolated from the leaves of Monodora brevipes Benth. (Annonaceae). Among them, one new natural indole named 5-formylindole (1) and three known aporphine alkaloids: (+)-roemeroline (2); (+)-corydine (3) and (+)-menispermine (4). They were isolated for the first time from this species. The structures of these compounds were established according to their spectral data (NMR, SM, IR and UV). Eric et al., International Current Pharmaceutical Journal, June 2017, 6(7): 40-43 http://www.icpjonline.com/documents/Vol6Issue7/01.pdf